The Effect of Financial Distress, Company Size, Earning Persistence, and Profitability on Accounting Conservatism - Farid , Satria Rachman; Zakaria, Adam; Handarini, Dwi (LPPM Universitas Negeri Jakarta, 2022)
This study aims to investigate the effect of financial distress, firm size, earning persistence, and profiability on accounting conservatism. This research is a quantitative research and uses secondary data which consists of financial reports. The dependent variable in this research is accounting conservatism. The independent variables in this research are financial distress, firm size, earning persistence, and profiability which measures by ROA. The unit of analysis and population which use in this research are companies which categorized in sector Consumer Non-Cyclical subsector beverages and processed food listed on Indonesia Stock Exchange for periods of 2017 – 2021. This research uses pusposive sampling method amounting 76 observation datas in type of unbalanced panel data. The results in this research are financial distress and profitability partially have a negative effect on accounting conservatism. Whereas, firm size and earning persistence partially do not affect the accounting conservatism. Based on those results, a companies which have a high level of financial distress are tend to loosen their accounting conservatism because the high level of financial distress is a bad news for investors and creditors whilst managers will attend to cover up this issue by loosen the accounting conservatism. Companies which have a high level of profitability will tend to loosen the accounting conservatism to manage their existence on public. Companies which have a low level of profitability are tend to strengthen the accounting conservatism as the evaluation material of the issue on low level profitability. For investors and creditors, this research is expected to be a refference for business decision. For manager, this research is expected to be a refference on implementation of accounting conservatism policy.